Division of Polynomial by quadratic

There was a question in which it was asked to find the remainder when x100x^{100} is divided by x23x+2x^2-3x+2. However I somehow manged to solve this question. But then I thought what would be the general case of this; that is---

What is the remainder when f(x)f(x) is divided by

i) (xa)(xb)(x-a)(x-b)

ii) ax2+bx+cax^2+bx+c

(Provided that f(x)f(x) is of degree 2\geq 2

Note by Kishlaya Jaiswal
7 years, 8 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

i) Let Q(x)Q(x) and R(x)R(x) be the quotient and remainder respectively when f(x)f(x) is divided by (xa)(xb)(x-a)(x-b).

Write f(x)=(xa)(xb)Q(x)+R(x)f(x) = (x-a)(x-b)Q(x)+R(x). Then, f(a)=R(a)f(a) = R(a) and f(b)=R(b)f(b) = R(b).

Since R(x)R(x) must be a linear polynomial, we have:

R(x)=bxbaf(a)+xabaf(b)=f(b)f(a)bax+bf(a)af(b)baR(x) = \dfrac{b-x}{b-a}f(a) + \dfrac{x-a}{b-a}f(b) = \dfrac{f(b)-f(a)}{b-a}x + \dfrac{bf(a) - af(b)}{b-a}.

Both expressions are equivalent, pick the one you like best.

ii) Write ax2+bx+c=a(xα)(xβ)ax^2+bx+c = a(x-\alpha)(x-\beta), then use part i).

Jimmy Kariznov - 7 years, 8 months ago

Log in to reply

Sorry, I didn't understand how did you got the expression for R(x)R(x)

But this is how I solved it -

f(x)=q1(xa)+r1f(x)(xa)=q1+r1(xa)...(i)f(x) = q_1(x-a) + r_1 \Rightarrow \frac{f(x)}{(x-a)} = q_1 + \frac{r_1}{(x-a)} ...(i)

f(x)=q2(xb)+r2f(x)(xb)=q2+r2(xb)...(ii)f(x) = q_2(x-b) + r_2 \Rightarrow \frac{f(x)}{(x-b)} = q_2 + \frac{r_2}{(x-b)} ...(ii)

where r1=f(a),r2=f(b)r_1 = f(a) , r_2 = f(b)

Now subtracting the equation (i) from equation (ii) we get -

f(x)(ba)(xa)(xb)=(q1q2)+(r2xr1x+r1br2a)(xa)(xb)f(x)\frac{(b-a)}{(x-a)(x-b)} = (q_1 - q_2) + \frac{(r_2x - r_1x + r_1b - r_2a)}{(x-a)(x-b)}

Therefore the remainder when f(x)f(x) is divided by (xa)(xb)(x-a)(x-b) must be (r2xr1x+r1br2a)ba\frac{(r_2x - r_1x + r_1b - r_2a)}{b-a}

Placing the values of r2=f(b)r_2 = f(b) and r1=f(a)r_1 = f(a), we get -

f(b)f(a)bax+bf(a)af(b)ba\frac{f(b) - f(a)}{b-a}x + \frac{bf(a) - af(b)}{b-a}

I didn't understand that why are we getting the quotient as q1q2q_1 - q_2

(Please tell me if I went wrong somewhere)

Kishlaya Jaiswal - 7 years, 8 months ago

Calculation of Remainder when x100x^{100} is divided by x23x+2x^2-3x+2

We know that when p(x)p(x) is divided by g(x)g(x). Then q(x)q(x) is quotient and r(x)r(x) is remainder

Where Degree of r(x)r(x) is less then q(x)q(x)

So Using Division algorithm, p(x)=q(x)g(x)+r(x)p(x) = q(x)\cdot g(x)+r(x)

So here p(x)=x100p(x) = x^{100} and g(x)=(x23x+2)=(x1)(x2)g(x) = (x^2-3x+2) = (x-1)\cdot (x-2) and Let r(x)=ax+br(x) = ax+b

So Degree of r(x)<r(x) < Degree of g(x)g(x)

So x100=(x1)(x2)g(x)+ax+b.................................................[1]x^{100} = (x-1) \cdot (x-2)\cdot g(x)+ax+b.................................................[1]

Put x1=0x=1x-1 = 0\Rightarrow x = 1

1=0+a+b............................................[2]1 = 0+a+b............................................[2]

Put x2=0x=2x -2 = 0\Rightarrow x = 2

2100=0+2a+b...................................[3]2^{100} = 0+2a+b...................................[3]

Now solving [2][2] and [3][3], we get

a=21001a = 2^{100} - 1 and b=22100b = 2-2^{100}

So r(x)=(21001)x+(22100)r(x) = (2^{100}-1)\cdot x +(2-2^{100})

jagdish singh - 7 years, 8 months ago
×

Problem Loading...

Note Loading...

Set Loading...